OC-052 Universal Screening For Alcohol Misuse In Acute Medical Admissions Is Feasible And Identifies Patients At High Risk Of Liver Disease. (9th June 2014) - Meredith, P; Schmidt, P; Atkins, S; Greengross, P; Westwood, G; Aspinall, R
Abstract : Introduction: The 2013 NCEPOD report into deaths from Alcohol Related Liver Disease (ARLD) highlighted missed opportunities for detecting alcohol misuse in recurrent hospital admissions. Universal screening of medical patients was advised but little is known of the achievability of this or its efficiency at detecting high risk cases. In 2011, Portsmouth Hospitals NHS Trust introduced a 7-day Alcohol Specialist Nursing Service (ASNS) coupled with universal screening of medical patients using a novel electronic data capture system. We present data on the feasibility of unselected screening and the resulting alcohol profiles of over 28, 000 medical admissions in a large acute hospital serving a catchment of 650, 000. Methods: From July 2011 to December 2012, all admissions via the Acute Medical Unit (AMU) were screened using the VitalPAC clinical observation system with a VitalPAC Alcohol Assesment Score (VPAAS) based on the Paddington Alcohol Test. At-risk patients (VPAAS of 6 or more) were referred to the ASNS and an Alcohol Use Disorders Identification Test (AUDIT) performed. Data analysis was performed on patient demographics, unit consumption, diagnosis, mortality and previous ED attendances and admissions. Results: There were 29, 361 admissions of whom 28, 098 (96%) completed VPAAS alcohol screening. Mean AMU population age was 67.4 years, 52.3% female. Of 1, 123 high risk cases, 770 were seen by the ASNS and 636 defined as dependent (AUDIT >20). Compared to the general AMU cohort, the at-risk group had more ED attendances (7.8 vs. 2.9) and hospital admissions (4.8 vs. 3.1) in the previous 3 years and a lower age of death (58.3 vs. 81.5). Dependent women had fewer recurrent attendances and admissions than men but had a higher mortality rate and lower age of death (52.2 vs. 62.4). The maximum AUDIT score of 40 was recorded in 41% of cases seen by the ASNS and this subgroup had a mean age of death of 52.7 with 6.2 admissions and 10.8 ED attendances previously. The most frequent primary diagnoses in those with a VPAAS of 6+ were liver disease, mental health disorders and GI bleeding. Conclusion: Our analysis of over 28, 000 admissions demonstrates that screening of all medical patients for alcohol misuse is achievable. We successfully identified a cohort of high risk patients with recurrent admissions and ED attendances, high unit consumption and an elevated risk of liver disease and early death. This cohort can be targeted with interventions to reduce the burden of alcohol related harm. Disclosure of Interest: P. Meredith: None Declared, P. Schmidt Conflict with: Unpaid research advisor to The Learning Clinic Ltd that created and licences use of VitalPAC, S. Atkins: None Declared, P. Greengross Conflict with: Part-time Medical Director of The Learning Clinic Ltd that created and licences the use of VitalPAC, G. Westwood: None Declared, R. Aspinall: None Declared.